Constructing Social Identity through Language: The English Influence in Production of MSMES - Fauzi, Deri Fikri; Haryani, Heni (ITScience (Information Technology and Science), 2024)
This study explores the significant role of English language usage in the production practices of Micro, Small, and Medium Enterprises (MSMES) in Indonesia, particularly focusing on how this linguistic choice reflects social identity within a globalized context. By examining prevalent English terms in product naming—such as